Social responsibility as a driver for local sustainable development - Elena Costantino; Maria Paola Marchello; Cecilia Mezzano (Fondazione Eni Enrico Mattei (FEEM), 2010)
The increased interconnection among local and global players induced by globalization, as well as the need for a complete application of the 'subsidiarity principle', calls for a re-thinking of the 'corporate social responsibility' concept. This new concept broadens the perspective of the single company interacting with its own stakeholders in relation to specific social and environmental impacts, to a network of organizations, with different aims and natures, collaborating on relevant sustainability issues. In this paper, the authors will provide a definition of 'Territorial Social Responsibility', sustaining the multi-stakeholder approach as a driver toward local sustainable development. Firstly, theoretical approaches to sustainable development at the territorial level will be examined, identifying the most innovative ideas about governance, network relation and development theories. The idea of development focuses not only on the economic aspects, but on the structural and institutional factors. The existence of cooperative territorial networks is essential to fulfil the creation of tangible and intangible assets at the local level. At the same time, the effectiveness of the decision-making and rules' system can stimulate and empower territorial networks to tackle sustainable development. An analytical framework, scheme-shaped, will be set in order to identify the main aspects, indicators and practices characterizing the territorial social responsibility concept. It will represent a first attempt to create a feasible instrument aimed at understanding how cooperative social responsible actors, operating in the same territory, could direct the path toward sustainable development.
Keywords: M14; O10; 330; Local Sustainable Development; Territorial Social Responsibility; Participation; Local Governance; Accountability; Sustainability Reporting; Multi-Stakeholder Approach; Networks